Graft‐Versus‐Host Disease Following Liver Transplantation: Development of a High‐Incidence Rat Model and a Selective Prevention Method. Issue 4 (22nd November 2016) - Yu, E.; Ueta, H.; Kimura, H.; Kitazawa, Y.; Sawanobori, Y.; Matsuno, K.
Abstract : Graft‐versus‐host disease (GvHD) following liver transplantation (LT) is a rare but serious complication with no presently available animal model and no preventive measures. To develop a rat model of GvHD after LT (LT‐GvHD), we preconditioned hosts with sublethal irradiation plus reduction of natural killer (NK) cells with anti‐CD8α mAb treatment, which invariably resulted in acute LT‐GvHD. Compared with those in the peripheral counterpart, graft CD4 + CD25 − passenger T cells showed lower alloreactivities in mixed leukocyte culture. Immunohistology revealed that donor CD4 + T cells migrated and formed clusters with host dendritic cells in secondary lymphoid organs, with early expansion and subsequent accumulation in target organs. For selectively preventing GvHD, donor livers were perfused ex vivo with organ preservation media containing anti‐TCRαβ mAb. T cell–depleted livers almost completely suppressed clinical GvHD such that host rats survived for >100 days. Our results showed that passenger T cells could develop typical LT‐GvHD if resistant cells such as host radiosensitive cells and host radioresistant NK cells were suppressed. Selective ex vivo T cell depletion prevented LT‐GvHD without affecting host immunity or graft function. This method might be applicable to clinical LT in prediagnosed high‐risk donor–recipient combinations and for analyzing immunoregulatory mechanisms of the liver. Abstract : The authors describe an animal model of graft‐versus‐host disease following liver transplantation and its selective prevention method without pan‐immunosuppression.